Social capital and migrants. - Zadeh, Behzad Saheb; Ahmad, Nobaya (EuroJournals, 2009)
This study is focused on social capital and migrant. How migrant communities develop and use the principles of social capital, and how such capital affects their potential to integrate them in their day-to-day activities. Social capital is something useful that exists among individuals of community that will be operationally perceived cooperation among them as “glue” or “connect” humans to achieve theirs goals .Trust, networks, norms, values and collective action are seen as resources that facilitate coordination and cooperation among individuals. Social capital has an impact and influence on migrant. It is often used to explain the success and well-being of societies, communities or individuals.This study explores some of the ways in which social capital is created by a migrant community. Social capital furnishes migrant individuals and families with resources beyond their individual reach by creating connections and support while living in a foreign country. For a variety of noted reasons, generally life is easier in a community blessed with a substantial stock of social capital. This is theoretical research that method of collection of data is document method. Studies have shown that social capital among migrant communities are stronger compared when they are in their home country. Due to common culture, language, value, and specific ritual and custom, we hope to observe aspect of social trust, networks, norms, values and collective action among migrant communities.